Citric acid–enhanced Fe2+ and Cu2+ synergistic activation of persulfate for rhodamine B degradation - Yujing Lin; Xudong Wang; Hongmin Zhang; Yongtao Lv; Licheng Chen; Shumiao Cao (Desalination and Water Treatment)
Citric acid (CA) and Cu2+ were used to enhance Fe2+-activated persulfate (PDS) for rhodamine B (RhB) oxidative degradation. The effects of PDS concentration, Fe2+ concentration, CA concentration, Cu2+ concentration, pH, and common inorganic anions in water on PDS activation and RhB degradation were investigated. Results showed that sulfate and hydroxyl radicals were the primary active substances in the reaction system, with sulfate radical playing a key role. The addition of CA and Cu2+ improved the efficiency of RhB decomposition, achieving a removal rate of 98.4% after 30 min of reaction, governed by pseudo-first-order. The presence of a complexing agent, allows effective RhB removal over a wide pH range. The free sulfate radical (SO4·−) concentration increases with increasing Fe2+ concentration. However, when the Fe2+ concentration was higher than 0.5 mM, self-quenching of SO4·− occurred and the RhB degradation rate decreased. In contrast, with increasing PDS concentration, the degradation rate of RhB continued to increase. The radical process was the main mechanism of RhB decomposition. Analysis of intermediates showed that C–C and C–N bond cleavage was the most likely degradation mode for contaminants to become small molecules.